Aspects of violence : a critical theory - Schinkel, Willem, 1976- (Basingstoke [England] : Palgrave MacMillan, 2010)
'While most analyses don't define violence and regard it as an essentially contested concept, this book argues for an ontological definition of violence as a reduction of being. This enables a critical sociology to move beyond tacit acceptance of a historically contingent definition of violence as profferred by the state'--Provided by publisher.
The Concept and Observation of Violence. Introduction: Aspects of Violence -- The Definition of Violence Part I -- The Definition of Violence Part II -- The From Critique of Violence to Autotelic Violence: Re-Reading Walter Benjamin -- Violence in social science. The Will to Violence -- The continuation of violence by other means : terrorism -- A Note on Causes of High School Violence -- Defining Terrorism -- The Trias Violentiae -- For a New Social Science of Violence.
Includes bibliographical references and index.
Keywords: Violence